'All of us are Presidents': Radical democracy and citizenship in the Chapare Province, Bolivia1. (March 2013) - Grisaffi, Thomas
"All of us are presidents" examines the promise and disappointments of direct democracy that followed Evo Morales' election as president of Bolivia. Working with the literature on politics, the state, and social movements in Latin America, the author contrasts ideas of normative democracy with radical democracy. The article pursues two ideas. First, in the wake of Morales' election his core political base in the Chapare region perceived and engaged in politics as if they exercised direct, structural authority over the president's policies. Second, while Morales initially embraced direct democracy he quickly distanced himself from this practice. As the coca growers observe, Morales abandon their political practices they have ceased to refer to themselves as presidents. Therefore, the author suggest that the model of direct democracy that Morales and his aides have promoted is in fact nothing more than a stark utopian claim designed to ensure the legitimacy of the MAS party.